2022
DOI: 10.1111/nph.18552
|View full text |Cite
|
Sign up to set email alerts
|

Root placement patterns in allelopathic plant–plant interactions

Abstract: Plants actively respond to their neighbors by altering root placement patterns. Neighbormodulated root responses involve root detection and interactions mediated by root-secreted functional metabolites. However, chemically mediated root placement patterns and their underlying mechanisms remain elusive.We used an allelopathic wheat model system challenged with 60 target species to identify root placement responses in window rhizobox experiments. We then tested root responses and their biochemical mechanisms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
0
20
1
Order By: Relevance
“…Common examples of allelopathic disturbances are that allelopathic and invasive plants release chemicals to inhibit the growth of weeds and native plants [ 21 , 24 , 25 , 26 ]. Meanwhile, a recent study also demonstrated that allelochemicals mediated root placement patterns in interspecific interactions [ 27 ]. For facilitation, the nitrogen fixation and phosphorus mobilization of legumes modifies the root morphogenesis of other plants, thereby achieving interspecific facilitation in traditional intercropping systems [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common examples of allelopathic disturbances are that allelopathic and invasive plants release chemicals to inhibit the growth of weeds and native plants [ 21 , 24 , 25 , 26 ]. Meanwhile, a recent study also demonstrated that allelochemicals mediated root placement patterns in interspecific interactions [ 27 ]. For facilitation, the nitrogen fixation and phosphorus mobilization of legumes modifies the root morphogenesis of other plants, thereby achieving interspecific facilitation in traditional intercropping systems [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants can adjust biomass allocation and root traits as well as root placement patterns in response to different neighbors associated with various soil types 5,36,42 . In the current study, rice had different responses to penoxsulam‐resistant and ‐susceptible barnyardgrass.…”
Section: Discussionmentioning
confidence: 64%
“…Effective strategies involve plant–plant chemical signaling through the release of compounds that trigger defensive responses in neighboring plants (Wilkinson et al ., 2019; Zhang et al ., 2020; Karban, 2021). Recent studies have shown that neighbor‐induced allelochemical response can be driven by the root‐secreted signal (−)‐loliolide (Kong et al ., 2018; Li et al ., 2020; Wang et al ., 2023). In this study, (−)‐loliolide upregulated the expression of defensive metabolite biosynthesis genes and activated defense‐related signaling pathways, inducing the production of defensive metabolites against herbivores, pathogens, and competitors in several plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the root‐secreted carotenoid metabolite, (−)‐loliolide, functions as a general soilborne signal for neighbor detection that induced an allelochemical response in wheat and rice exposed to many competing species (Kong et al ., 2018; Li et al ., 2020; Wang et al ., 2023). (−)‐Loliolide also acted as an endogenous inducer of herbivore resistance in tomato and Arabidopsis aboveground (Murata et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%